Conductive Two‐Dimensional Phthalocyanine‐based Metal–Organic Framework Nanosheets for Efficient Electroreduction of CO2. (23rd June 2021) - Yi, Jun‐Dong; Si, Duan‐Hui; Xie, Ruikuan; Yin, Qi; Zhang, Meng‐Di; Wu, Qiao; Chai, Guo‐Liang; Huang, Yuan‐Biao; Cao, Rong
Abstract: The electrocatalytic conversion of CO2 into value‐added chemicals is a promising approach to realize a carbon‐energy balance. However, low current density still limits the application of the CO2 electroreduction reaction (CO2 RR). Metal–organic frameworks (MOFs) are one class of promising alternatives for the CO2 RR due to their periodically arranged isolated metal active sites. However, the poor conductivity of traditional MOFs usually results in a low current density in CO2 RR. We have prepared conductive two‐dimensional (2D) phthalocyanine‐based MOF (NiPc‐NiO4 ) nanosheets linked by nickel‐catecholate, which can be employed as highly efficient electrocatalysts for the CO2 RR to CO. The obtained NiPc‐NiO4 has a good conductivity and exhibited a very high selectivity of 98.4 % toward CO production and a large CO partial current density of 34.5 mA cm −2, outperforming the reported MOF catalysts. This work highlights the potential of conductive crystalline frameworks in electrocatalysis. Abstract : Nickel phthalocyanine molecules as active sites were installed into nickel‐catecholate‐linked 2D conductive metal–organic framework nanosheets for efficient CO2 electroreduction with nearly 100 % CO selectivity.